2017
DOI: 10.1038/ncb3478
|View full text |Cite
|
Sign up to set email alerts
|

A mechanically active heterotypic E-cadherin/N-cadherin adhesion enables fibroblasts to drive cancer cell invasion

Abstract: Cancer-associated fibroblasts (CAFs) promote tumour invasion and metastasis. We show that CAFs exert a physical force on cancer cells that enables their collective invasion. Force transmission is mediated by a heterophilic adhesion involving N-cadherin at the CAF membrane and E-cadherin at the cancer cell membrane. This adhesion is mechanically active; when subjected to force it triggers β-catenin recruitment and adhesion reinforcement dependent on α-catenin/vinculin interaction. Impairment of E-cadherin/N-cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
522
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(550 citation statements)
references
References 70 publications
25
522
2
1
Order By: Relevance
“…Cadherins usually participate in homophilic interactions, 9 but heterophilic adhesion complexes involving E-cadherin and Ncadherin between cancer-associated fibroblasts and cancer cells drive cooperative tumor invasion. 33 Collective cell migration is the coordinated movement of cells connected by cell-cell adhesion, and is a fundamental process in development, tissue repair, tumor invasion and metastasis. [34][35][36] Neoplastic cells across several cancers can display collective migration without incurring epithelial-to-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…Cadherins usually participate in homophilic interactions, 9 but heterophilic adhesion complexes involving E-cadherin and Ncadherin between cancer-associated fibroblasts and cancer cells drive cooperative tumor invasion. 33 Collective cell migration is the coordinated movement of cells connected by cell-cell adhesion, and is a fundamental process in development, tissue repair, tumor invasion and metastasis. [34][35][36] Neoplastic cells across several cancers can display collective migration without incurring epithelial-to-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…This remains in line with previous studies, in which no significant changes between tumor and LNMs concerning fibroblast immunopositivity for ras homolog family member A (RHOA), Rac family small GTPase 1 (RAC1) (20), αSMA, S100 calcium binding protein A4 (S100A4) and vimentin (21) were observed. Both our own and the above-mentioned results speak in favor of the hypothesis (formulated based on animal model) suggesting that stromal components of primary tumor (the soil) could be brought by metastatic cells (the seed) and could influence the process of metastasis formation (1)(2)(3) . To the best of our knowledge, our report is the first to compare expression of podoplanin in CAFs of primary tumor and synchronous LNMs.…”
Section: Expression Of Alpha Smooth Muscle Actin (αSma) (A-c) and Pmentioning
confidence: 61%
“…Moreover, co-traveling stromal cells can increase the viability of circulating metastatic cancer cells and provide them with an early growth advantage (1). It was also shown that CAFs promote tumor invasion by exerting a physical force on cancer cells, enabling them to escape from the primary site (2) . The identification of CAFs in peripheral blood from patients with metastatic breast cancer confirms the hypothesis suggesting co-travel of stromal and cancer cells during formation of metastases (3).…”
mentioning
confidence: 99%
“…These junctions comprise E-cadherin from the cancer cell and N-cadherin located on the CAF membranes, and their maturation requires actomyosin modulation. Importantly, through these junctions, CAFs exert mechanical forces on cancer cells, which allows invasion of cancer cells to occur (Labernadie et al, 2017).…”
Section: Cell Migrationmentioning
confidence: 99%